Análise da Eficiência de Compressão do Codificador HEVC Embarcado no Smartphone Samsung Galaxy S23 Plus - Costa, Vítor; Perleberg, Murilo; Agostini, Luciano; Porto, Marcelo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16013, 2025)
The consumption of video content on mobile devices is becoming increasingly integrated into people’s daily routines. The intensive transmission of video between devices requires smartphones to include dedicated embedded hardware capable of performing real-time video encoding and decoding. Due to the high computational demands of the video encoding process, dedicated hardware designs must implement various resource-constraining strategies to reduce computational complexity. These constraints inevitably impact the rate-distortion performance, leading to a loss in coding efficiency. This study aims to analyze the constraints and their effects on the coding efficiency of the Qualcomm Snapdragon 8 Gen 2 chipset, embedded in the Samsung Galaxy S23 Plus smartphone. The results of this work can help hardware designers assess whether the coding efficiency losses introduced by their solutions align with those observed in commercial video encoders.